2017
DOI: 10.1101/230771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A role for the Tgf-β/Bmp co-receptor Endoglin in the molecular oscillator that regulates the hair follicle cycle

Abstract: The hair follicle is a biological oscillator that alternates growth, regression and rest phases driven by the sequential activation of the proliferation/differentiation programs of resident stem cell populations. The activation of hair follicle stem cell niches and subsequent entry into the growing phase is mainly regulated by Wnt/β-catenin signalling, while regression and resting phases are mainly regulated by Tgf-β/Bmp/Smad activity. A major question still unresolved is the nature of the molecular switch tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Therefore, it is rare to identify the regulators which could mediate the downstream molecules simultaneously feedback regulation of TGF-β and BMP signaling pathways in the same cell type, tissue or during the same biological process. A recent study reported that Endoglin, a common non-canonical receptor of TGF-β and BMP signaling pathways, could regulate both of two signaling pathways [11]. However, little is known whether the core members feedback regulate these two signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is rare to identify the regulators which could mediate the downstream molecules simultaneously feedback regulation of TGF-β and BMP signaling pathways in the same cell type, tissue or during the same biological process. A recent study reported that Endoglin, a common non-canonical receptor of TGF-β and BMP signaling pathways, could regulate both of two signaling pathways [11]. However, little is known whether the core members feedback regulate these two signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus, R-SMAD/SMAD4 transcription complex regulates the spatial and temporal expression of target genes, usually along with other modulators and co-regulators such as transcription factors (e.g., βcatenin [11]), transcription co-factors including co-activators (e.g., p300/CBP [36]), and co-repressors (e.g., Ski and SnoN [37]). However, the roles of SMAD4 in the interaction with these co-regulators are quite different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface glycoprotein endoglin (Eng) is a receptor for the Tgf‐β pathway known to modulate the crosstalk between Bmp and Wnt signalling in the hematopoietic system during early development 61,62 . Recently, it has been found to serve a similar function in HFSC during adult homeostasis, where mice with reduced whole‐body expression of Eng exhibited dissonant hair growth patterns and out‐of‐sync expressions of hair cycle regulators such as Bmp4, Noggin and Shh 63 . Further analysis revealed Wnt effector β‐catenin and Bmp effector Smad4 forming heterodimers to drive Eng expression, suggesting the communication between Wnt/β‐catenin and Tgf‐β/Bmp/Smad signalling pathways in HFSCs during homeostasis 63 …”
Section: Transcription Factors and Signalling Pathways Acting In Quiementioning
confidence: 99%
“…It has been reported to bind several different TGFβ superfamily ligands, including BMP9 and TGFβ1 6 and it has two alternative spliced protein isoforms that differ in their short cytoplasmic tails 7 . The ENG gene is positively regulated by BMP/SMAD signaling 810 . Under pathological situations, such as preeclampsia or inflammation, endoglin may be shed from the cell surface by metalloproteases resulting in soluble circulating S-endoglin 11, 12 that can act as a ligand trap.…”
Section: Introductionmentioning
confidence: 99%